2010
DOI: 10.1590/s1678-77572010000400017
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage in conservative cavities varying the preparation method and surface treatment

Abstract: ObjectiveTo assess microleakage in conservative class V cavities prepared with aluminum-oxide air abrasion or turbine and restored with self-etching or etch-and-rinse adhesive systems.Material and MethodsForty premolars were randomly assigned to 4 groups (I and II: air abrasion; III and IV: turbine) and class V cavities were prepared on the buccal surfaces. Conditioning approaches were: groups I/III - 37% phosphoric acid; groups II/IV -self-priming etchant (Tyrian-SPe). Cavities were restored with One Step Plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Numerous studies show that even when attempting to bond the material to a cavity preparation, the marginal seal is typically compromised, resulting in marginal gaps, stains, or leakage [49,50]. This deficiency remains true even with current "improved" adhesive systems [51][52][53]. In fact most in vitro leakage studies have shown that dental composites do not provide a perfect seal to either enamel or dentin, independent of bonding or placement method [54].…”
Section: Polymerization Stress -In Vitro Evidencementioning
confidence: 99%
“…Numerous studies show that even when attempting to bond the material to a cavity preparation, the marginal seal is typically compromised, resulting in marginal gaps, stains, or leakage [49,50]. This deficiency remains true even with current "improved" adhesive systems [51][52][53]. In fact most in vitro leakage studies have shown that dental composites do not provide a perfect seal to either enamel or dentin, independent of bonding or placement method [54].…”
Section: Polymerization Stress -In Vitro Evidencementioning
confidence: 99%
“…bacteria, fluids, molecules, or ions between a cavity wall and the restoration [4]. Different approaches have been introduced in an attempt to decrease microleakage during the adhesiverestorative procedures such as the application of different curing strategies, the reduction of polymerization shrinkage by the incremental layering technique, the use of flowable composites, the surface treatment, and the development of new adhesive systems [5][6][7][8][9]. However, these measures have not been able to prevent microleakage completely.…”
Section: Introductionmentioning
confidence: 99%
“…[46] This finding was in agreement with those of previous similar studies. [13,14,39,47,48] At the gingival margins, the bonding groups presented the lowest microleakage scores. However, none of the materials tested were completely resistant to dye penetration (leakage) at the gingival margins.…”
Section: Discussionmentioning
confidence: 97%